Vascular endothelial growth factor-A promoter polymorphisms, circulating VEGF-A and survival in acute coronary syndromes - Palmer BR; Paterson MA; Frampton CM; Pilbrow AP; Skelton L; Pemberton CJ; Doughty RN; Ellis CJ; Troughton RW; Richards AM; Cameron VA (PLOS, 2021)
BACKGROUND: Development of a competent collateral circulation in established coronary artery disease is cardio-protective. The vascular endothelial growth factor (VEGF) system plays a key role in this process. We investigated the prognostic performance of circulating VEGF-A and three genetic variants in the VEGFA gene in a clinical coronary cohort. METHODS AND RESULTS: The Coronary Disease Cohort Study (CDCS) recruited 2,140 patients, with a diagnosis of acute coronary syndrome (ACS), after admission to Christchurch or Auckland City Hospitals between July 2002 and January 2009. We present data for 1927 patients from the cohort genotyped for three SNPs in the VEGF-A gene, rs699947 (C-2578A), rs2010963 (C405G) and rs3025039 (C936T). Plasma VEGF-A concentrations were assayed in a subgroup (n = 550) of CDCS patients (geometric mean 36.6 [34.7-38.5] pg/ml). VEGF-A levels correlated with patient heart rate at baseline (p = 0.034). None of rs699947, rs3025039, nor rs2010963 genotypes were significantly associated with VEGF-A levels, but rs3025039 genotype was positively associated with collateral vessels perfusion according to the Rentrop classification (p = 0.01) and baseline natriuretic peptide levels (p<0.05). Survival in the CDCS cohort was independently associated with baseline VEGF-A levels and (in males) with rs699947 genotype. CONCLUSIONS: This study is strongly suggestive that VEGF-A levels have value as a prognostic biomarker in coronary heart disease patients and SNPs in VEGF-A deserve further investigation as prognostic markers and indicators of angiogenic potential influencing the formation of collateral circulation.
This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Keywords: Acute Coronary Syndrome; Cohort Studies; Humans; Middle Aged; Polymorphism, Single Nucleotide; Vascular Endothelial Growth Factor A